Investment resources of the pension systems of Kazakhstan and the Russian Federation: current situation and development prospects - Zemtsov, А.А.; Sembekov, A.K.; Budeshov, Ye.G. (BUKETOV BUSINESS REVIEW, 2017)
The article examines the role of the pension sector in the country's economy, its role in shaping the country's economic security. This part also analyzes the investment directions of pension savings of the Russian Federation and pension resources of the Republic of Kazakhstan for the period under study. The study showed that the following points underlie the identified problem moments of investment activity in the portfolio of the Unified Accumulative Pension Fund (hereinafter – UAPF) as a single operator of the pension system: in general, an inefficient and conservative low yield of the structure of investment portfolios is observed, as well as lack of quality investment instruments. The largest part of pension assets is directed to finance the deficit of the state budget of the country, thereby pension savings of citizens are exposed to general economic risks. In order to solve the above problems, the article proposes to apply more actively the progressive world experience in the transition to the active investment strategy of the UAPF. The article proposes measures to increase the activation of the infrastructure direction in the investment activity of the Unified Accumulative Pension Fund of the Republic of Kazakhstan, and also make changes in the Investment declaration of the UAPF, to expand the use of pension assets in the financing of infrastructure projects to increase investment income of the UAPF portfolio with the subsequent transition to an active investment strategy. A list of measures is also proposed, the implementation of which would create conditions for the activation of the AUPF in this direction.